Post-Synthetic Regulation of HS Structure: The Yin and Yang of the Sulfs in Cancer - Vives, Romain R.; Seffouh, Amal; Lortat-Jacob, Hugues (Frontiers in Oncology, 2014)
Heparan sulfate (HS) is a complex polysaccharide that takes part in most major cellular processes, through its ability to bind and modulate a very large array of proteins. These interactions involve saccharide domains of specific sulfation pattern (S-domains), the assembly of which is tightly orchestrated by a highly regulated biosynthesis machinery. Another level of structural control does also take place at the cell surface, where degrading enzymes further modify HS post-synthetically. Amongst them are the Sulfs, a family of extracellular sulfatases (two isoforms in human) that catalyze the specific 6-O-desulfation of HS. By targeting HS functional sulfated domains, Sulfs dramatically alter its ligand binding properties, thereby modulating a broad range of signaling pathways. Consequently, Sulfs play major roles during development, as well as in tissue homeostasis and repair. Sulfs have also been associated with many pathologies including cancer, but despite increasing interest, the role of Sulfs in tumor development still remains unclear. Studies have been hindered by a poor understanding of the Sulf enzymatic activities and conflicting data have shown either anti-oncogenic or tumor-promoting effects of these enzymes, depending on the tumor models analyzed. These opposite effects clearly illustrate the fine tuning of HS functions by the Sulfs, and the need to clarify the mechanisms involved. In this review, we will detail the present knowledge on the structural and functional properties of the Sulfs, with a special focus on their implication during tumor progression. Finally, we will discuss attempts and perspectives of using the Sulfs as a biomarker of cancer prognosis and diagnostic and as a target for anti-cancer therapies.